Cytotoxicity and Antibacterial Activity of Toothpastes and Mouthwashes Available in the Iranian Market - Zahra Shahidi; Shiva Tavakol Davani; Faranak Noori; Masoumeh Hasani Tabatabaei; Fatemeh Sodeif; Ardavan Etemadi; Nasim Chiniforush; Zohreh Moradi (Frontiers in Dentistry, 2021)
Objectives: Toothpastes and mouthwashes contain chemicals that may be harmful to oral tissues. This study assessed the cytotoxicity and antibacterial activity of toothpastes and compare the Iranian and foreign toothpastes and mouthwashes available in the Iranian market in this respect. Materials and Methods: Twenty samples (13 toothpastes and 4 mouthwashes) were selected. The cytotoxicity of 1, 10, and 50 mg/mL of toothpastes and 0.05, 2 and 10 µL of mouthwashes was measured after 1, 15 and 30 min of exposure to human gingival fibroblasts, each in triplicate. The methyl thiazolyl tetrazolium (MTT) assay was used for cytotoxicity testing. The serial dilution method was utilized to determine the minimum inhibitory concentration (MIC) of each sample against Lactobacillus acidophilus (L. acidophilus) and Streptococcus mutans (S. mutans). Two-way ANOVA and Tukey’s test were used for data analysis. Results: A significant difference in cytotoxicity was noted among different products (P=0.00). The difference in cytotoxicity of each sample was not significant at 1, 15 and 30 min (P=0.08). The obtained MIC for all toothpastes and mouthwashes was between 0.0039 mg/mL and 0.0156 mg/mL, except for Sensodyne toothpaste and Oral B mouthwash. Conclusion: Some brands of toothpastes have higher cytotoxicity due to their composition, and their cytotoxicity should not be overlooked. The antibacterial activity of the samples was almost equal when they were in contact with L. acidophilus and S. mutans except for the Irsha mouthwash, Sehat, Darugar and Bath toothpastes. The antibacterial effect of toothpastes and mouthwashes increased with an increase in exposure time.